2015
DOI: 10.17523/bia.v72n1p69
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes using different distances for preconditioning for the male effect in Anglo Nubian goats during two distinct climate seasons

Abstract: The objective of the present study was to determine if separation distance between bucks and does during two distinct climate seasons could affect the reproductive performance of goats subjected to a 45-day mating season (MS). Anglo Nubian does (n = 120) were kept apart from bucks at distances of 2 m (T1), 300 m (T2), and 2000 m (T3) for 60 days prior to the 45-day MS during two distinct climate seasons [dry season (DS, February to March) . In summary, the separation distance between bucks and does did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…This fact is in accordance with previous data in goats and sheep (aLvEs et al, 2014;CaLdas et al, 2015), as described by CusHwa et al (1992) and pEarCE and oLdHaM (1988), who reported efficient estrous detection. In accordance with Martin et al (1986), two peaks of estrous detection were observed when males were introduced into the ewe herd, which was in seasonal anestrous.…”
Section: Discussionsupporting
confidence: 93%
“…This fact is in accordance with previous data in goats and sheep (aLvEs et al, 2014;CaLdas et al, 2015), as described by CusHwa et al (1992) and pEarCE and oLdHaM (1988), who reported efficient estrous detection. In accordance with Martin et al (1986), two peaks of estrous detection were observed when males were introduced into the ewe herd, which was in seasonal anestrous.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, prolonged anestrus postpartum is a limiting factor to livestock production as it negatively affects reproductive rates and overall profitability. On the other hand, anestrus can be easily minimized by adopting appropriate management practices such as the male effect [7,22], which is low cost, easily implemented and fits within animal welfare criteria [1,2,4,5,9,13]. Additionally, the male effect may be used as a breeding tool to select females with higher reproductive potential as it has been shown to be associated with reduced age at first delivery and interval between deliveries and increased number of multiple deliveries [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…Por isso é importante racionalizar a eficiência reprodutiva dos rebanhos através do desenvolvimento de estraté-gias que sejam de baixo custo e fácil execução [4]. Nesse contexto, o controle dos eventos reprodutivos contribui para maximizar o manejo reprodutivo, a correta indução e sincronização do estro, seja através de fármacos [11,26] ou por métodos naturais, como o efeito macho [1][2][3]5], que são ferramentas para acelerar o melhoramento genético tendo em vista que permitem concentrar as coberturas em curto período de tempo, os partos ocorrem em épocas favoráveis, além de contribuírem para implementação de programas de reprodução assistida, como a inseminação artificial [23,25] e a transferência de embriões [17].…”
Section: Introductionunclassified